Pengalaman Perawat IGD Merawat Pasien Do Not Resuscitate pada Fase Perawatan Menjelang Ajal - Maria Imaculata Ose (Jurnal Keperawatan Indonesia, 2017)
Do Not Resuscitate (DNR) menjadi keputusan yang tidak mudah diambil oleh dokter dan membutuhkan pertimbangan dan rekomendasi dari perawat. Keterbatasan pengalaman, pengetahuan dan informasi DNR, kriteria IGD yang lebih berfokus pada perawatan gawat darurat menyebabkan tidak dapat maksimalnya peran perawat dalam perawatan menjelang ajal. Tujuan penelitian ini adalah mengeksplorasi pengalaman perawat di IGD dalam merawat pasien DNR di ruang IGD. Desain Penelitian dengan metode Kualitatif pendekatan Fenomenologi interpretif, partisipan empat perawat IGD. Data dikumpulkan melalui Indepth interview, menggunakan analisis tematik Braun dan Clark. Hasil Penelitian empat tema yaitu 1. Memahami kegagalan resusitasi merupakan pasien DNR, 2. Melakukan resusitasi sebagai Protap Penanganan awal, 3. Berkolaborasi mengambil keputusan DNR, 4. Menyiapkan kematian pasien dengan baik. Kesimpulannya yaitu pengambilan keputusan DNR (Do Not Resuscitate) membutuhkan pertimbangan dan pemahaman pada kriteria DNR, selain itu perawat harus terlibat dalam kolaborasi dengan tim yang merawat pasien, sehingga keputusan DNR tepat. Perawatan DNR di IGD memberikan resusitasi sebagai tindakan awal dan mempersiapkan kematian pasien dengan baik dengan melibatkan keluarga pasien. Abstract Experience of ER Nurse in Treating Do Not Resuscitate Patients in End of Life Care Phase. Do Not Resuscitate (DNR) is a difficult decision for doctors to make. In making the decision, the doctors need to consider nurses’ recommendation. Due to limited knowledge, experiences, and information of DNR, plus the criteria of emergency department which are only focused on emergency treatments, the nurses cannot maximize their roles in the end of life care. This study, thus, aimed to explore the nurses’ experiences in the emergency rooms especially in taking care of DNR patients. This research employed a qualitative method that was interpretive phenomenology approach involving four nurses who were working in the emergency department. Data was collected through in depth interview, using thematic analysis suggested by Braun & Clark. The results of the study cover four themes; they are to 1. Understand the failure of resuscitation during the treatment, 2. Perform resuscitation as an early standard operating procedure to treat patients 3. Collaborate in making decision on DNR, 4. Prepare patients for a good death. The conclusion is before deciding to perform DNR (Do Not Resuscitate), doctors need to understand the criteria of DNR and get nurses involved in it. DNR treatment in the emergency rooms is an early standard operating procedure to treat patients at the end of life phase and to prepare them for a good death by also engaging their family members.   Keywords: DNR, end of life care, emergency of nursing